A large single-center prospective study to investigate the factors influencing the choice of breast-conserving surgery versus mastectomy in Chinese women with early breast cancer - Zhensheng Li; Yunjiang Liu; Jing Zhang; Yue Li; Kaiye Du; Shuo Zhang; Huina Han; Jun Zhang (World Journal of Surgical Oncology, 2023)
Abstract Background Compared to mastectomy, breast-conserving surgery (BCS) provides the same survival rate and a higher quality of life for patients with early breast cancer (EBC). However, Chinese women with EBC are known to have a low BCS rate. A large prospective cohort study was conducted to investigate the factors influencing the choice of BCS in this population. Methods In 2017, all women with unilateral EBC and eligible for BCS at our institution were enrolled. Before surgery, the patient’s trust in the surgeon and her perceived strength of the surgeon’s recommendation of BCS were measured through an in-person interview and validated ad hoc questionnaire. Multivariate logistic regressions on BCS procedure vs. mastectomy were used to estimate the odds ratio (OR). Results One thousand one hundred thirty-six patients enrolled at analysis had an average age of 51.8 and tumor size of 2.4 cm. 19.9% of patients had BCS. The “strong” level of trust in the surgeon was significantly associated with BCS with an OR of 2.944 (p<0.001) when compared to the “average or under” trust. The “strong” and “moderate” strengths in surgeon recommendation for BCS were also found to be significantly associated with the BCS procedure with ORs of 12.376 (p <0.001) and 1.757 (p =0.040), respectively, compared to the “neutral or dissuaded” strength. Conclusions Stronger trust in surgeons and BCS recommendation by surgeons are associated with a higher rate of BCS in Chinese women with EBC. Interventional trials are needed to confirm this finding.